Estudo de uma Instituição sem fins lucrativos de cuidados reabilitacionais e sua relação com as políticas de saúde - Rutigliano, Maria Eunice Cardoso de Castro Nobrega (2014)
This is a case study with a qualitative approach about the Rehabilitation Center for Child Cerebral Palsy from Guarujá (CRPI), which is a philanthropic center of interdisciplinary rehabilitation. CRPI institutional mission is to increase social inclusion of children and teenagers with neuro-sensory-motor deficiencies, with an emphasis on families from Great Santos area. The center is a nonprofit institution that began its activities in 1963 at the residence of the founder Steffi Leonore Asch, in Guaruja. The theme of this study was chosen because of the importance of providing philanthropic institutions in the Brazilian social safety net. The goal is to reconstruct the trajectory of the CRPI, from its foundation to the present day, and research how it coordinates with the Brazilian public policies, particularly in the health and social fare fields. It was conducted a literature review focused on the public policies of social security and health care since the times of pre Federal Constitution, enacted in 1988 with the creation of the Sistema Único de Saúde (SUS), or Unified System for Health Care, including a a brief history of the creation of rehabilitation centers in Brazil. Besides the literature review, the study conducted structured and semi-structured interviews with 17 professionals of the institution and collected historical data available in the archives of the center, newspapers and official sites of the city of Guarujá. It was concluded that the institution followed the changes in public health policy and education, moving from a simply welfare institution to one with awareness about the policies of rights; from serve a population with only preserved cognition level to serve children with multiple disabilities. It also started to approach the public resources, especially with the current grant from the City of Guarujá and through partnerships with the Departments of Health and Education, which brought a situation of mutual dependence, or symbiosis, between CRPI and the Government of Guarujá. Key